2008
DOI: 10.1007/s11104-008-9580-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of solution Cd2+ concentration in metal-contaminated soils as affected by soil temperature: consequences on lettuce (Lactuca sativa L.) exposure

Abstract: The aim of this study was to assess how the solubility and the speciation of Cd in soil solution were affected over time by the soil temperature for three metal-contaminated soils. The changes of solution Cd concentration (either total or free ionic) and other physico-chemical parameters (e.g. pH, ionic strength, the concentrations of NO À 3 , SO 2À 4 , Ca, Mg and dissolved organic carbon) were monitored over a 28-day culture of lettuce (Lactuca sativa L.) in soils incubated at 10°C, 20°C or 30°C. The major re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Its impact has been extensively reported for Cd (e.g. Fotovat and Naidu, 1998;Sauve et al, 2000;Cornu et al 2008). Solution pH (Table 1) increased over the culture period by about 0.4 pH unit (P b 10 − 8 ).…”
Section: Solution Phmentioning
confidence: 72%
See 1 more Smart Citation
“…Its impact has been extensively reported for Cd (e.g. Fotovat and Naidu, 1998;Sauve et al, 2000;Cornu et al 2008). Solution pH (Table 1) increased over the culture period by about 0.4 pH unit (P b 10 − 8 ).…”
Section: Solution Phmentioning
confidence: 72%
“…Thereby, temperature can impact on the mobility of metals via modulating the soil microbial activity. This was clearly observed by several authors (Almas et al, 1999;Qureshi et al, 2003;Cornu et al, 2008). In the context of global climate change, the need to assess the impact of temperature on the mobility of metals in soil has become essential.…”
Section: Introductionmentioning
confidence: 85%
“…El incremento de la toxicidad para el Cd en el andisol, periodo 2 de incubación, en el cual la concentración es menor, lo cual puede atribuirse a una posible desnitrificación (Cornu et al 2008), así como a un cambio del potencial redox, al aumento de la conductividad eléctrica de la solución, y que por aumento de la acidez, este metal pudo generar el desplazamiento de las sales de los sitios de intercambio de los coloides del extracto acuoso, generando la inhibición del crecimiento de las plántulas (Rodríguez-Serrano et al 2008). …”
Section: Resultados Y Discusiónunclassified
“…Likewise, the level of cadmium (Appendix A-Tables A1 and A2), also exceeded the minimum values established by the regulations for water for human consumption; studies have been reported where the exposure of L. sativa to this metal causes toxic and harmful effects that decrease its growth as the concentration of Cd, and thereby its adsorption, increases [59][60][61]. Just as the presence of heavy metals and cyanide has toxic implications in the plant and animal model, in the same way, it will affect the health of the human being [62,63].…”
Section: Lactuca Sativamentioning
confidence: 91%